THE ROLE OF MODERN EDUCATIONAL TECHNOLOGIES IN ORGANIZING GENDER-SENSITIVE EDUCATION IN HIGHER EDUCATION INSTITUTIONS - Yakhyayeva Sojida Abdurakhimovna (Bright Mind Publishing, 2025)
This article outlines the role of modern educational technologies in the organization of gender-oriented education in higher education institutions, the main criteria for achieving gender equality and the formation of civil society.
Keywords: Education, science, technology, student, gender equality, attitude, progress, system.